Analysis of repeat content in the genomes of green algae and early land plants - Nazare, Teodora (Jihočeská univerzita, 2022)
Genomes of 12 plant species ranging from uni-cellular green algae to land plants are analyzed using the Repeat Explorer 2 computational tool. The repetitive elements distribution and annotation is obtained and compared withing the 12 plant species
Analysis of repeat content in the genomes of green algae and early land plants
Keywords: plant; repeats; mobile elements; plant; repeats; mobile elements